Assessing the post-COVID prospects for the energy transition in the Netherlands and the UK, using a policy barriers approach. Issue 6 (3rd June 2022) - Todd, Iain; Bulder, Cas; McCauley, Darren; Burns, Mary-Kate
ABSTRACT: Before the COVID crisis, the Netherlands and the UK were embarking on national energy transitions away from fossil fuel systems. However, the arrival of the pandemic unequivocally altered the trajectory of energy transitions on a global scale. Every country in the world is now grappling with the twin challenges of the COVID crisis and the climate crisis, and there is a grave risk that the short-term demands of the former could eclipse the vital long-term actions needed to address the latter. While there is optimism that green economic recoveries will propel energy transitions through investments, there is an urgent need to assess and address any new policy barriers which COVID poses to achieving them. To do so, in the summer of 2020, researchers conducted pairs of interviews with 30 experts within the social and energy sectors, involving government, industry and third sector stakeholders. Key research questions sought to identify the policy barriers acting – inadvertently or otherwise – to disrupt that balance between tackling COVID and the energy transition, and the mechanisms available to restore the necessary equilibrium. Through a structured analysis of policy barriers to the energy transition post-COVID, we assess its delivery in both countries. We derive a new taxonomy and definition of policy barriers. We also generate a suite of 10 policy recommendations, which were placed in priority order by the interviewees themselves. The paper concludes with observations on those recommendations, the differences noted between the two countries, and the validity of using policy barriers for policy analysis.